PELAKSANAAN PENGELOLAAN KEARSIPAN PADA PT WILO PUMPS INDONESIA JAKARTA UTARA - Irawan, Roy; Dewi, Intan Kusuma; Prana, Indra; Wijaya, Darma (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
PT Wilo Pumps Indonesia is a supplier company in the field of building services, water management, and industry. Has a wide range of products, especially pumps for building service markets, water management markets, and industrial markets. Wilo is synonymous with high efficiency, high quality, and reliable products. Product innovation regularly sets new standards in terms of energy efficiency and sustainability in the handling of natural resources. Public and private sector organizations, in administrative activities will always be associated with archives. The organization’s archive procedures can provide information that is important and needed for the running of the organization. With the increasing activity and dynamics of the organization, it will bring a tendency to increase the need for information to support the decision-making process to achieve goals. The data collection method in the preparation of this article is the method of observation, interviews, and literature study with the analytical method in the form of qualitative analysis, namely the method of data analysis without using static analysis. The results of the implementation of archive management at PT Wilo Pumps Indonesia through the receptionist, secretary, and archivist. Implementation of archive management in the form of sorting, naming documents, indexing, inputting, and storing.